The effect of adiabatic temperature on the control combustion product - 274947 Yeoh, Sim Teik (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1999